2019
DOI: 10.3390/w11102069
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder Farmers’ Adaptation to Drought: Identifying Effective Adaptive Strategies and Measures

Abstract: One of the biggest challenges for South African food security is recurring drought. It is a major concern due to insufficient knowledge and the low levels of resources or livelihood assets available to farmers in vulnerable situations, thereby limiting coping and adaptation choices. The objective of this paper was to identify the current adaptation and coping measures used by smallholder farmers, with a particular emphasis on farmers’ vulnerability to drought and the adaptive measures or strategies that are ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
22
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 38 publications
9
22
1
3
Order By: Relevance
“…The strength of the livelihood capitals in enhancing the resilience of smallholder farmers in this study for the Northern Cape Province differed from what Muthelo et al [47] found for smallholder livestock farmers in the Free State Province of South Africa. They found Free State province of South Africa smallholder farmers have high economic resilience capital followed by social, natural and human capitals.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The strength of the livelihood capitals in enhancing the resilience of smallholder farmers in this study for the Northern Cape Province differed from what Muthelo et al [47] found for smallholder livestock farmers in the Free State Province of South Africa. They found Free State province of South Africa smallholder farmers have high economic resilience capital followed by social, natural and human capitals.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, smallholder farmers' welfare was highly influenced by the economic resources available to the farmer, as indicated by the highly significant estimate of economic capital. This is consistent with the finding of Muthelo et al [47] in the Free State Province of South Africa. Another important capital with a high effect on welfare of smallholder farmers was social capital.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Maximum temperatures in October (Figure 10 Although the SQMK detected several other possible change points after the year 2002 as noted by the crossing of the u(t) and u 0 (t) curves, a significant increasing trend at a 95% confidence level was detected to have developed around 2015 in October and 2016 in November. This is in agreement with the drought experienced in South Africa around the 2015/2016 period, which was one of the driest periods in South Africa (Muthelo et al 2019). The minimum temperature, which also exhibited increasing trends in November, showed that the increasing trend started in 1997 (insignificant) and the trend turned significant in 2001 (Figure 10(c)).…”
Section: Sequential Mann-kendall Testsupporting
confidence: 89%
“…In this study, the term 'droughtcoping' refers to short-term interventions adopted during the drought, while 'adaptation' strategies are those interventions done to prepare for future droughts. Unfortunately, SHFs struggle to cope and adapt to drought without assistance from governmental and private institutions (Muthelo et al, 2019). This requires innovative approaches, which include knowledge-sharing and organisations and institutions to devise plans that will facilitate adaptation among SHFs (Muthelo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%